PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PERENCANAAN ANGGARAN DAN POLITIK PENGANGGARAN, DENGAN TRANSPARANSI PUBLIK SEBAGAI VARIABEL MODERATING TERHADAP SINKRONISASI DOKUMEN APBD DENGAN DOKUMEN KUA - PPAS PADA PEMERINTAH KABUPATEN ACEH TENGGARA - Dudi Iskandar; Rina Bukit; Idhar Yahya (Program Magister Akuntansi Unsyiah, 2013)
The purpose of this study was to look at the influence of the capacity of human resources, budget planning and budgeting politics on the synchronization between Regional Revenues and Expenditures Budget (APBD) document and General Policy of Regional Revenues and Expenditures Budget (KUA) - Provisional Budget Ceiling Priority (PPAS) document and to test the role of public transparency in moderating the relationship between the capacity of human resources, budget planning, budgeting politics with the synchronization between APBD document and KUA-PPAS document. The population of this study was 123 persons consisting of legislative members and officials/employees who were involved in the preparation of the Work Plan and Budget of 29 Regional Apparatus Working Units and all of them were selected to be the samples for this study by using census sampling method. The data used in this study were primary data obtained through the questionnaires directly distributed to the respondents. The data obtained were analyzed through multiple linear regression tests and interaction test. Hypothesis was simultaneously and partially tested through F test and t test. The result of hypothesis test in this study showed that simultaneously the variables of capacity of human resources, budget planning and budgeting politics had a positive and significant influence on the synchronization between APBD document and KUA-PASS document, and partially, capacity of human resources and budgeting politics had a significant influence on the synchronization between APBD document and KUA-PASS document while budget planning had a negative and signifcant influence. The result of the interaction test showed that public transparency could not moderate the relationship between the capacity of human resources, budget planning and budgeting politics and the synchronization between APBD document and KUA-PASS document. Keywords : APBD, KUA, PASS, Human Resource Capacity, Budget Planning, Budgeting Politics, Public Transparency